Analysis of BOS Fund Usage in Public Elementary Schools Gunung Talang District, Solok Regency - Yeni Adam, Siska; Mecia Melia; Hadiyanto; Yahya (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze the differences in the utilization of the School Operational Assistance (BOS) fund between large- and small-scale public elementary schools in Gunung Talang Subdistrict, Solok Regency. The research subjects include SDN 20 Koto Gaek Guguk (large school) and SDN 22 Jawi-Jawi (small school). A descriptive qualitative approach was employed using interviews, observations, and document analysis. The findings indicate that school scale significantly affects the strategy and effectiveness of BOS fund utilization. Large schools tend to be more innovative in allocating funds for quality improvement programs, while small schools focus more on basic operational needs. SWOT analysis reveals distinct strengths, weaknesses, opportunities, and threats in each school, leading to relevant strategic recommendations. The study suggests the need for more proportional and affirmative funding policies for small schools to ensure equitable educational services.